Coronavirus in the (bio)political imaginarium - Perić Diligenski, Tijana D. (Sociološki pregled, 2020)
The paper starts from the premise that (bio)political engineering of conservatively profiled political actors during the coronavirus (SARS-CoV-2) pandemic was determined by economic calculations. The coronavirus imaginarium exposed the logic of the neoliberal market economy and pointed to the need to deconstruct the existing and establish a new economic paradigm. The findings of the paper show that the pandemic has brought to light an infection of non-solidarity and intolerance towards the phenomenon of otherness, which is accused of being a contagious factor. The paper elaborates that democratic ways of governing are overshadowed by populist manners that tend to use the narrative of fear of viruses to consolidate their own regimes.